International Conference on Small and Medium Scale Enterprises, 28-30 May, 1990, Pulau Langkawi - International Conference on Small and Medium Scale Enterprises (1990 : Pulau Langkawi); Universiti Utara Malaysia ([S.l.] : [s.n.], 1990)
36